Olive Cultivation 2022
DOI: 10.5772/intechopen.102769
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Olive Leaf Extract on Systolic and Diastolic Blood Pressure in Adults: A Systemic Review and Meta-Analysis

Abstract: Hypertension (HTN) is one of the most common disorders and increases the risk of cardiovascular diseases (CVD), which are one of the main causes of death in the world. The Mediterranean diet has the efficacy to modulate CVD risk factors such as HTN, mainly because of olive tree products, which are the most pivotal ingredients in this diet. Among the olive tree products, olive leaf consists of many sorts of phenolic compounds and has several beneficial effects on human body, such as antioxidant, anti-atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Oleuropein is the most commonly described polyphenolic compound. A large number of studies in humans and laboratory rats have demonstrated its antihypertensive activity [ 90 , 91 ]. Olive leaf polyphenols have been shown to lower diastolic and systolic blood pressure in prehypertensive and hypertensive groups of patients [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Anti-stroke Action Of Olive Polyphenolsmentioning
confidence: 99%
“…Oleuropein is the most commonly described polyphenolic compound. A large number of studies in humans and laboratory rats have demonstrated its antihypertensive activity [ 90 , 91 ]. Olive leaf polyphenols have been shown to lower diastolic and systolic blood pressure in prehypertensive and hypertensive groups of patients [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Anti-stroke Action Of Olive Polyphenolsmentioning
confidence: 99%